Papaya Breeding for Tolerance to Bacterial Decline (Erwinia sp.)in the Caribbean Region - Ollitrault, P.; Bruyère, S.; Ocampo, J.; de Lapeyre, L.; Gallard, A.; Argoud, L.; Duval, M.F.; Duval, M.F.; Le Bellec, F.
Papaya has a great potential for agricultural diversification in the Caribbean region, because of its rusticity, rapid production, high yields and the wide demand on local and international markets. At the end of the 1960s, a disease caused by Erwinia sp. appeared in the West Indies. This 'bacterial decline' decimated all the papaya fields in the area, where the cultivar 'Solo' was grown for its high yields and good quality. The disease is found from Virgin Islands to Venezuela. Tolerant accessions have been previously identified in the regional germplasm, however tolerance sources generally showed poor fruit quality and dioecy. A breeding project has been implemented by CIRAD in Guadeloupe to select good quality cultivars with improved level of tolerance. The first step was analyzing morphological and genetic diversity of regional germplasm, as compared with some commercial cultivars. Morphological diversity is important, but shows no particular structure, while isozyme diversity is more limited but displays some geographic structure. The level of tolerance to Erwinia strains appeared variable in relation with the tested papaya families, the Erwinia strains and the environmental conditions. However the rank for tolerance of the families remains the same whatever the strains and the environmental conditions. Tolerance appears to be transmitted in a co-dominant way in F1 hybrids between cultivar Solo and tolerant accessions. Selection of tolerant hermaphrodite lines is going on through backcross and endogamy strategies.
Keywords: BACTERIAL CANKER; ISOZYME; GENETIC RESOURCES; GUADELOUPE